Protein O-mannosylation in the early secretory pathway. (August 2016) - Neubert, Patrick; Strahl, Sabine
Graphical abstract: Highlights: O -Mannosylation initiates at the translocon complex in the endoplasmic reticulum (ER). O -Man glycans can mark and exclude unfavorable folding intermediates (UPOM). O -Mannosylation is an integral part of the interlinked ER protein homeostasis network. New insights from high throughput MS-based glycoproteomics are discussed. Abstract : Protein O -mannosylation and N -glycosylation are essential post-translational modifications, which initiate in the endoplasmic reticulum (ER). In yeast, the two glycosylation machineries act at the Sec61 translocon complex where they can even compete for certain substrate proteins. N -linked glycans play a crucial role in the ER quality control of glycoproteins. In recent years, it became clear that in addition to its important functions for cell surface proteins, O -mannosylation impacts the ER protein homeostasis. These glycans can exclude unfavorable folding intermediates from futile folding attempts, increase the solubility of irreversibly misfolded proteins, and even mark them for degradation. O -Mannose glycoproteomics now captures the molecular complexity of this modification opening exciting opportunities to explore further roles of O -mannosylation in the early secretory pathway.